: VIGART APPLICATION TO ASSIST ASD CHILDREN (International Journal of Engineering and Computer Science, 2017)
Children with Autism Spectrum Disorder (ASD) are often characterized by inadequacy in social communication skills. In recent time, many assistive technologies, particularly Virtual Reality, have been investigated to promote social. It is well known that children with ASD demonstrate atypical viewing patterns during social interactions and thus monitoring eye-gaze can be valuable to design intervention strategies. While several researchers have used eye-monitoring technology to track eye-gaze for analysis, there exists no real time system that can monitor eye-gaze dynamically and provide customized feedback. Researchers are increasingly employing technology to develop more feasible, accountable, and individualized intervention tools to address core vulnerabilities related to autism. The study states the development and preliminary application of a Virtual Reality (VR) technology aimed at facilitating improvements in social communication skills for adolescents with autism. Virtual Interactive system with Gaze-sensitive Adaptive Response Technology (VIGART) is capable of delivering individualized feedback based on a child’s dynamic gaze patterns during VR-based interaction. I present preliminary data from the usability study of this technological application for six adolescents with autism and discuss potential future development and application of adaptive Virtual Reality technology within an intervention framework.